Efek Pemberian Ekstrak Jamur Shiitake (Lentinula Edodes) Terhadap Aktivitas Superoksida Dismutase Pada Tikus Yang Diinduksi Karbon Tetraklorida - Cici Farhana Ambarwanty Mohtar; Suci Indah Budiarti (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2021)
Shiitake mushrooms (Lentinula edodes) is edible mushrooms and medicinal mushrooms because they contain high nutrients and bioactive compounds, such as flavonoids, phenols and terpenoids that can function as antioxidants. Antioxidants are molecules that are able to ward off free radicals in the body, although naturally the body can ward off free radicals through enzymatic (endogenous) antioxidants, such as superoxide dismutase (SOD). But if too many free radicals enter the body, it can cause oxidative stress so that endogenous antioxidants cannot work properly, so exogenous antioxidants are needed such as those found in ethanol extracts of L. edodes. One of the materials that can become free radicals is carbon tetrachloride (CCl4). This study aims to determine the effect of ethanol extract of L.edodes on levels of SOD, in rats and determine the most effective dose of ethanol extract on increasing levels of SOD and blood catalase in rats induced by CCl4. This research carried out experimentally with a Completely Randomized Design (CRD) with variation of ethanol extract concentration (250; 500; 750 ppm). The results showed that the extraction of shiitake mushroom extract has an effect on increase in the levels of superoxide dismutase and catalase in rats induced carbon tetrachloride. The concentration of ethanol extract of 500mg/kg BW of rats was the most effective concentration for increasing superoxide dismutase and the ethanolic extract of L. edodes had antioxidant activity.